Changes in serum albumin and other nutritional markers when using sucroferric oxyhydroxide as phosphate binder among hemodialysis patients: a historical cohort study - Kalantar-Zadeh, Kamyar (BMC Nephrol, 2019)
BACKGROUND: Elevated serum phosphorus concentrations are common among maintenance hemodialysis patients. Protein is a major source of dietary phosphate, but restriction of protein intake can result in hypoalbuminemia and protein-energy wasting. We hypothesized that sucroferric oxyhydroxide (SO), a potent phosphate binder with a low pill burden, may reduce serum phosphorus levels in hemodialysis patients with hypoalbuminemia without adversely impacting albumin levels or dietary intake of protein. METHODS: We retrospectively examined de-identified data from 79 adult, in-center hemodialysis patients with baseline hypoalbuminemia (≤ 3.5 g/dL) switched to SO as part of routine clinical care for at least 1 year. Temporal changes (3-month intervals from baseline through Q4) in phosphate binder pill burden, serum phosphorous levels, nutritional markers, and equilibrated Kt/V were analyzed. Data from a matched reference group of non-hypoalbuminemic patients (N = 79) switched to SO were also examined. RESULTS: SO therapy was associated with a mean reduction of 45.7 and 45.1% in daily phosphate binder pill burden, and a mean reduction of 0.4 mg/dL and 0.51 mg/dL in serum phosphorus levels for the hypoalbuminemic and non-hypoalbuminemic patients, respectively. Hypoalbuminemic patients demonstrated significant increases in mean serum albumin levels from 3.50 mg/dL at baseline to 3.69, 3.74, 3.70, and 3.69 mg/dL during Q1 through Q4, respectively (P < 0.0001), whereas serum albumin levels remained unchanged in the non-hypoalbuminemic group. CONCLUSIONS: Both hypoalbuminemic and non-hypoalbuminemic patients switching to SO exhibited significant reductions in serum phosphorus concentrations and daily phosphate binder pill burden. Among hypoalbuminemic patients, the initiation of SO therapy was also associated with increases in serum albumin, suggesting therapy may have allowed patients to increase their dietary intake of protein.